DNS of droplet impact on a solid particle: Effect of wettability on solid conjugate heat transfer. (September 2020) - Das, Saurish; Panda, A.; Patel, H.V.; Deen, N.G.; Kuipers, J.A.M.
Highlights: Studies are carried out by Direct Numerical Simulations of droplet spreading on solid particle. Solid is resolved using Immersed Boundary Method whereas the droplet motion is resolved using Volume of Fluid Method. Static contact angle boundary condition is enforced by coupling IBM-VOF. Nusselt number based on wetted surface area is defined to lump the effect of wettability. Solid conductivity was found to have a larger effect on the overall heat transfer rate. Abstract: Heat transfer between solid particles and liquid droplets is a key phenomenon encountered in many industrial applications. We investigate the fluid dynamics and heat transfer between a liquid droplet and a static solid particle by means of direct numerical simulations. The presence of the solid particle is represented through a sharp interface immersed boundary method (IBM) on a Cartesian computational grid, whereas the motion of the gas-liquid interface is tracked by a mass conservative volume of fluid method (VOF). To account for the thermal coupling between the gas and the liquid, and more specifically the conjugate heat transfer between the fluid and the solid, a second order accurate diffused interface formulation is proposed for the conduction term in the energy equation. A detailed validation of the method is also presented. We have studied the effect of wettability and solid conductivity both of which have been found to have significant effect on the total heat transfer rate.